(untitled) (Research, Society and Development, 2021)
Diagnoses, as well as all other phases of the nursing process (NP), play a fundamental role in the evolution of the client, they guide all planning of the nursing team on the implementation of care that meets the specific needs of all patients in the health and illness process. This work, had a objectives raise with the professional nurses, the level of knowledge about the nursing diagnoses and its relationship from the perspective of nursing process and nurging theories. It was a qualitative field research, having nurses as research subjects, directly linked to assistance, in tertiary care of a hospital in the interior of São Paulo, who addressed the knowledge of these professionals about the nursing diagnoses importance. The 18 (100%) participants, only 4 (22,22%) answered that they based on Theory NHB by Wanda de Aguiar Horta and use electronic printouts from Nanda-I Taxonomy. The others 14 (77,77%), couldn’t answer. The search for humanized care and a scientifically embased profession, it’s necessary for all care practice, the nursing diagnoses that is the phases of NP are essential for all evolution of the patients, but many times the nursing diagnoses not applied correctly, how was it possible to verify with the data and opinion obtained in this study.